(untitled) (The Research of Medical Science Review, 2025)
Approximately 7.2 billion people around the world consume 136.2 million tons of fish annually. The need for fish meat and proteins intake increases day by day because most of the human population fulfils their proteins deficiency using fish meat and fish proteins. As fish are living in water therefore, they are directly exposed to many pathogenic microorganisms inhabiting the water environments of farms or in wild conditions. A Gram-positive bacterium, S. aureus is the major cause of numerous infections in a wide range living things and food poisoning. For thousands of years, the seeds of N. sativa are traditionally used for their medicinal importance particularly for the cure of infectious diseases and as health promoter into the animal feed. In the current study, identified cultured strains of S. aureus were obtained and invitro antibacterial activity of aqueous extracts of Nigella sativa, Aloe barbadensis, Curcuma longa, Calotropis procera, and Kalanchoe daigremontiana was evaluated. In this study it was concluded that N sativa, A. barbadensis, C. procera and K. daigremontiana exhibit antibacterial potential against S. aureus isolated from fish. It is also revealed that both N. sativa, and A. barbadensis exhibit a remarkable antibiotic potential that is quite comparable to the modern antibiotic (Azithromycin).